Liolaemus grosseorum : Diet - Brizio, María Victoria (2019)
Liolaemus grosseorum is a member of the boulengeri group of Liolaemus and is an ovipa-rous and insectivorous mid-sized lizard (max SVL = 55 mm; Etheridge 2001. Cuad. Herpetol. 15:3–15). It is distributed in four of Argentina’s provinces: Mendoza, La Pampa, Neuquén, and Río Negro (Pérez et al. 2018. Cuad. Herpetol. 32:141–143).